’Make in India’: a Visionary Campaign of Government of lndia - Mittal , A.K.; Aggarwal, Vimal Kumar (Gyan Management Journal, 2015)
Make in India is an initiative of the Government of India, to encourage companies to manufacture their products in India. Prime Minister Narendra Modi had hinted towards the launch of Make in India Campaign in his Independence Day speech of 15 August 2014. It was launched on 25 September 2014 in a function at the Vigyan Bhawan. A young nation with 800 million people under age 35, India is brimming with optimism and confidence. The young people’s energy, enthusiasm and enterprise are India’s greatest strength. Unleashing those attributes is the present government’s biggest mission.